Bridging Dyadic Relationships to Group Dynamics: A Systematic Literature Review on the Integration of Leader–Member Exchange (LMX), Team–Member Exchange (TMX), and Organizational Differentiation - Asep Dana Saputra; Mutiarawan; Abdul Hadi (Journal of Strategic Innovation in Economics and Business, 2026)
In the hyper-competitive era of digital market disruption, strategic innovation is fundamentally contingent upon the architectural configuration of an organization's relational capital. This study investigates the critical cascade of vertical Leader–Member Exchange (LMX) into horizontal Team–Member Exchange (TMX) and evaluates the structural impact of LMX differentiation on group dynamics. Employing a rigorous mixed-methods architecture, this research integrates a Systematic Literature Review (SLR) guided by the PRISMA protocol with an advanced quantitative bibliometric network analysis of 500 high-impact articles sourced from Scopus and Web of Science. The empirical synthesis reveals that while isolated, high-quality LMX effectively drives exploitative operational efficiency, it is insufficient to sustain long-term exploratory innovation. Instead, robust TMX networks are mandatory to establish the psychological safety required to operationalize intellectual capital and navigate external market shocks. Furthermore, the findings demonstrate that LMX differentiation operates as an economic double-edged sword; although it is functionally necessary for the optimal allocation of strategic resources, it frequently precipitates destructive relational ambivalence and defensive knowledge-hiding behaviors if mismanaged. The analysis concludes that cultivating a rigorous procedural justice climate is the indispensable mediator for neutralizing this interpersonal friction. Ultimately, strategic executives must transition relationship management from a peripheral human resources function into a core dynamic capability, balancing meritocratic differentiation with dense horizontal cohesion to ensure institutional agility and sustainable competitive advantage.